A review of management styles - Zakaria, Noor Syakirah; Hashim, Mohd Khairuddin (2015)
As an area of research, management styles have been receiving much attention over the past decades. Management styles have attracted much interest due to the idea that they can influence organizational performance as well as affect how organizations are sustained. However, at the same time, questions concerning their universality, applicability and relevance have also been raised in the literature.Based on the review of previous studies, this paper attempts to identify not only the different styles of management but also to examine their focus and scope. Information from the review suggests that there are at least five common management styles and that they differ from one another.